Modelamento geológico do perfil de intemperismo e caracterização mineralógica, química e petrográfica dos litotipos primários da porção noroeste da mina de Boa Vista, Catalão-GO - Rocha, Vinicius [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This project had as object of study the northwest portion of Boa Vista mine operated by Anglo American Niobium Brazil Ltda., and it is located at the alkaline complex of Catalão II which is inserted in the geological context of the Alkaline Province Alto Paranaíba. This province is a major metallogenic province of Brazilian geological framework being responsible for a wide range of commodities, such as niobium, phosphate, rare earth, titanium, vermiculite and barite. The Boa Vista ore consists of weathering products on a stockwork of pyrochlore-nelsonite dykes injected in metasediments. In this context, this project sought to contribute to the understanding of the evolution, geometry and behavior of Nb2O5 content in the weathering profile of the northwest portion of the mine through modeling in three dimensions (3D). In addition, it sought the delimitation of the contact surface between soil and rock, the modeling of the mineralized envelopes with Nb2O5 content above 0.5%, and petrographic, chemical and mineralogical characterization of the unweathered bedrock. To this propose modeling of the area was made with Leapfrog software and descriptions of drill core, petrographic descriptions and semi-quantitative chemical characterization were made. The objectives proposed by the study were successfully achieved, in which the oxidized material package proved to be continuous, with maximum depth of 40 meters, and the boundary surface between oxidized rock and bedrock showed continuous and a isopach map was produced. It was found the presence of rare earth element minerals (ETR) such as monazite - (Ce, La, Th) (PO4) - and bastnasite - (Ce, La) CO3F. The mineral ore, pyrochlore, showed up in different shapes and textures associated with mineral growth and magmatic differentiation. The resources calculated by the solid content comprising greater or equal values than 0.5% of Nb2O5 was estimated at 19190.7 t ore 0.5% Nb2O5. The Nb resources whitin...

Este trabalho de conclusão de curso tem como objeto de estudo a porção noroeste da mina Boa Vista, operada pela empresa Anglo American Nióbio Brasil Ltda. e situada no complexo alcalino de Catalão II, o qual se encontra inserido no contexto geológico da Província Alcalina do Alto Paranaíba, uma importante província metalogenética do território brasileiro responsável por um conjunto variado de mineralizações, como: nióbio, fosfato, terra raras, titânio, vermiculita e barita. A mina Boa Vista tem seu minério constituído dos produtos de alteração intempérica sobre um stockwork de diques de pirocloro-nelsonito colocados em metassedimentos regionais. Nesse contexto, o presente trabalho buscou contribuir para o entendimento da evolução, geometria e comportamento dos teores de Nb2O5 no perfil de intemperismo da porção noroeste da mina através do modelamento em três dimensões (3D) do perfil de alteração. Além disso, buscou-se a delimitação da superfície de contato entre perfil intempérico e rocha (PI/RF), o modelamento dos envelopes mineralizados com teores de Nb2O5 acima de 0,5% - teor de corte estabelecido pela empresa mineradora e a caracterização petrográfica, química e mineralógica da rocha sã. Para tal, fez-se uso do software Leapfrog para o modelamento a partir dos dados fornecidos pela empresa mineradora e, também, foram feitas descrições de testemunhos de sondagem, descrições petrográficas e caracterização química semi-quantitativa com uso do Espectrômetro de Energia Dispersiva (EDS). Os objetivos propostos pelo trabalho foram atingidos com êxito, nos quais o pacote de material oxidado se mostrou contínuo e com profundidade máxima de 40 metros, bem como a superfície limítrofe entre rocha oxidada/rocha sã se mostrou contínua e a partir disso foi feito um mapa de isoespessura da mesma. Constatou-se a presença de minerais de elemento terras raras (ETR), como monazita - (Ce,La,Th)(PO4)...
Keywords: Sensoriamento remoto; Modelagem geologica; Niobio; Determinação mineralogica; Intemperismo; Petrologia; Espectrometro; Catalão (GO)